PEMERIKSAAN KADAR GULA, ASAM URAT DAN KOLESTEROL DARAH GRATIS UNTUK LANSIA DI KLINIK PRATAMA ASY SYIFA KOTA BENGKULU - Lala Foresta; Valentine Gunasari (Universitas Bengkulu, 2017)
The increasing of age followed by the decreasing of cell function which causes organ weakness, physical deterioration, as well as the appearance of some disease especiallydegenerative diseases, such as the increasing level of the glucose, uric acid, andcholesterol in the blood. At the beginning, usually those diseasesdo not indicate definitesymptomps, so they could be detected only if the complications and damages wereappeared. Delayed diagnosing and providing adequate treatment could increases the riskof mortality, morbidity, and disability on elderly, so it is necessary to do routine andperiodic examination of health on elderly to filter the onset of symptomps of the diseases.In this program we did the examination of blood level of glucose, uric acid, andcholesterol on elderly (> 60 years old) at Klinik Pratama Asy Syifa Kota Bengkulu tosocialize the importance of routine and periodic health examination for early detection ifcomes the problem in examination, and the adequate treatment could be given as soon aspossible.Keywords: elderly, examination, blood glucose, uric acid, cholesterol